PENGARUH LAMA PENGERINGAN DAN TEMPERATUR TERHADAP KONSUMSI BAHAN BAKAR LPG SELAMA PENGERINGAN IKAN BAGE TIPE TRAY DRYER: EFFECT OF DRYING TIME AND TEMPERATURE OF LPG FUEL CONSUMPTION DURING THE DRYING OF BAGE FISH TYPE TRAY DRYER - Muhammad Rifa'i (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Lemuru fish is a typical Sumbawa dish made from many types of fish and processed through various processes such as salting, salting and drying. The purpose of this research is the time and temperature of the drying process. The independent variables are: variations in temperature (50ºC, 60ºC, 70ºC) and time (180 minutes, 240 minutes, 300 minutes). After analysis, the following conclusions can be drawn. The drying speed is 180 minutes at 70°C. The highest drying speed was 0.98 g/minute, while the lowest was 300 minutes at 50 °C and a value of 0.56 g/minute. The air content temperature is 60⁰C and 70⁰C according to the quality standard for dried fish (SNI 82732016). Temperature 50 ⁰C 240 and time 300 minutes air content 32.67 n 28.33%. Drying time of 50% temperature 180 minutes gives 8.87% efficiency at lowest temperature 70ºC 300 minutes gives 3.64% The lowest material consumption is 180 minutes at 50ºC gives a value of 0.087 kg, the highest fuel consumption at 70ºC gets a value of 0.31 kg